Phf6-null hematopoietic stem cells have enhanced self-renewal capacity and oncogenic potentials - Hsu, Yueh-Chwen (Blood Adv, 2019)
Plant homeodomain finger gene 6 (PHF6) encodes a 365-amino-acid protein containing 2 plant homology domain fingers. Germline mutations of human PHF6 cause Börjeson-Forssman-Lehmann syndrome, a congenital neurodevelopmental disorder. Loss-of-function mutations of PHF6 are detected in patients with acute leukemia, mainly of T-cell lineage and in a small proportion of myeloid lineage. The functions of PHF6 in physiological hematopoiesis and leukemogenesis remain incompletely defined. To address this question, we generated a conditional Phf6 knockout mouse model and investigated the impact of Phf6 loss on the hematopoietic system. We found that Phf6 knockout mice at 8 weeks of age had reduced numbers of CD4(+) and CD8(+) T cells in the peripheral blood compared with the wild-type littermates. There were decreased granulocyte-monocytic progenitors but increased Lin(–)c-Kit(+)Sca-1(+) cells in the marrow of young Phf6 knockout mice. Functional studies, including competitive repopulation unit and serial transplantation assays, revealed an enhanced reconstitution and self-renewal capacity in Phf6 knockout hematopoietic stem cells (HSCs). Aged Phf6 knockout mice had myelodysplasia-like presentations, including decreased platelet counts, megakaryocyte dysplasia, and enlarged spleen related to extramedullary hematopoiesis. Moreover, we found that Phf6 loss lowered the threshold of NOTCH1-induced leukemic transformation at least partially through increased leukemia-initiating cells. Transcriptome analysis on the restrictive rare HSC subpopulations revealed upregulated cell cycling and oncogenic functions, with alteration of key gene expression in those pathways. In summary, our studies show the in vivo crucial roles of Phf6 in physiological and malignant hematopoiesis.